Living fossils and conservation values - Turner, Derek; Han, Junhyung (Frontiers in Earth Science, 2023)
Horseshoe crabs (Limulus polyphemus) have been in decline in Long Island Sound, and recently there has been discussion of whether the state of Connecticut should stop issuing licenses for commercial harvesting. This paper argues that in spite of concerns about the living fossil concept, the fact that the horseshoe crabs are living fossils should count in favor of more stringent protection. The paper distinguishes four different views about the status of the living fossil concept: 1) eliminativism; 2) redefinition; 3) reframing; and 4) conceptual pluralism. Approaches 2–4 all treat the criteria associated with living fossils as picking out distinctive features of evolutionary history. Those distinctive features of evolutionary history link up with conservation values in several ways. More generally, drawing upon relevant work in environmental philosophy, it is argued that evolutionary history is relevant to aesthetic and environmental value. Moreover, eliminativists have trouble rendering intelligible a striking pattern in the recent scientific literature. Researchers undertaking conservation-relevant work frequently highlight the living fossil status of the taxa under study.